Attending pediatric acutely ill patients at home: families' socioeconomic characterization, expectations, and experiences - Astrid Batlle; Santiago Thió-Henestrosa; Imma Boada; Sandra López; Isabel Moya; José Carlos Fernández; Mariona Fernández de Sevilla; Juan José García-García (BMC, 2022)
Abstract Background SJD a Casa is an acute pediatric hospital-at-home program that was initiated in 2019. For a thorough understanding of acute pediatric homecare programs, an analysis of all related factors, including the medical, social, and economic aspects as well as the family's experience, is essential. However, no previous study has attempted a comprehensive evaluation of this topic in relation to a complex program such as ours (in terms of the diseases and treatments offered). In this study, we aimed to finely characterize the population that opts for pediatric homecare programs and obtain a thorough understanding of the families' needs, which will improve our understanding of the program and potentially reveal possible deficiencies. Methods This prospective quantitative and qualitative study involved collection of ordinal data as well as statements made by the caregivers of patients undergoing homecare. A total of 372/532 families were asked to answer two independent questionnaires (preadmission and postadmission) that evaluated their socioeconomic characteristics; expectations and experiences; and factors influencing the preference for homecare. The results were presented as frequencies and comparisons (Fisher's exact test). Results The families had an adequate social network and a less-than-expected workload, and most families responded that they would have repeated the experience despite the workload. The expectations regarding the caregiver's well-being at home were better than the actual situation, since some caregivers experienced anxiety or fear. The rating for homecare was better than that for the inpatient care offered before the homecare transfer. Conclusions Families included in the program were content with the homecare program and mostly responded that they would repeat the experience if needed. Although the duration of the program was short-term, some caregivers may experience symptoms of burnout like anxiety, which should be taken into consideration. Despite its limitations, this study offers the possibility of improving our service portfolio by focusing on vulnerable families' access to the program and the caregiver's risk of burnout.